Bergmann glial AMPA receptors are required for fine motor coordination - Saab, Aiman S.; Jahn, Hannah Maria; Monyer, Hannah (Science, 2012)
The impact of glial neurotransmitter receptors in vivo is still elusive. In the cerebellum, Bergmann glial cells (BG) express α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-type glutamate receptors (AMPARs) composed exclusively of GluA1 and/or GluA4 subunits. Using conditional gene inactivation we found that the majority of cerebellar GluA1/A4-type AMPARs are expressed in BG. In young mice, deletion of BG AMPARs resulted in retraction of glial appendages from Purkinje cell (PC) synapses, increased amplitude and duration of evoked PC currents, and a delayed formation of glutamatergic synapses. In adult mice, AMPAR inactivation also caused retraction of glial processes. The physiological and structural changes were accompanied by behavioral impairments in fine motor coordination. Thus, BG AMPARs are essential to optimize synaptic integration and cerebellar output function throughout life.